Anisotropic properties of textured h-BN matrix ceramics prepared using 3Y2O3-5Al2O3(-4MgO) as sintering additives. Issue 5 (May 2019) - Zhang, Zhuo; Duan, Xiaoming; Qiu, Baofu; Yang, Zhihua; Cai, Delong; He, Peigang; Jia, Dechang; Zhou, Yu
Abstract: Textured hexagonal boron nitride (h-BN) matrix composite ceramics were prepared by hot pressing using 3Y2 O3 -5Al2 O3 (mole ratio of 3:5) and 3Y2 O3 -5Al2 O3 -4MgO (mole ratio of 3:5:4) as liquid phase sintering additives, respectively. During the sintering process with liquid phase environments, platelike h-BN grains were rotated to be perpendicular to the sintering pressure, forming the preferred orientation with the c -axis parallel to the sintering pressure. Both h-BN matrix ceramic specimens show significant texture microstructures and anisotropic mechanical and thermal properties. The h-BN matrix ceramics prepared with 3Y2 O3 -5Al2 O3 -4MgO possess higher texture degree and better mechanical properties. While the anisotropy of thermal conductivities of that prepared with 3Y2 O3 -5Al2 O3 is more significant. The phase compositions and degree of grain orientation are the key factors that affect their anisotropic properties.